Uji Organoleptik Pasta Gigi dengan Bahan Antiseptik dan Deodorizing dari Rebusan Jahe Merah (Zingiber Officinale Var. Rubrum) - Betty Saptiwi; Risya Cilmiaty; Muthmainah Muthmainah (Jurnal Kesehatan Gigi, 2020)
Red ginger (Zingiber officinale var. Rubrum) can effectively inhibit the growth of Aggregatibacter actinomycetemcomitans. Aside from containing active ingredients that are useful, the more value of red ginger is that it has a fresh, spicy taste, is easy to obtain and the price is cheap. So that when used as toothpaste, in addition to inhibiting the bacteria Aggregatibacter actinomycetemcomitans that cause periodontal disease, it can also refresh the throat and oral cavity. This study aims to describe and analyze organoleptic toothpaste with antiseptic and deodorizing ingredients from red ginger stew at concentrations of 25% and 50%. This type of research is analytic research that is pre-experimental with a one-shoot case study study design. The population in this study were students of the Postgraduate Masters of Nutrition Science Study Program of Sebelas Maret University Surakarta who had received organoleptic test training totaling 96 people. Samples were taken as many as 31 people with random sampling techniques. Data analysis uses Kendall Concordance statistical test. The results showed that the average preference for aroma, taste and overall toothpaste with a concentration of 50% (rank = 1.77, 1.81 and 6.14) was higher than toothpaste with a concentration of 25% (rank = 1, 23, 1.19, 3.86). Statistical test results also showed that respondents in tune / favor preferred toothpaste with a concentration of 50% rather than 25% (p = 0,000). The conclusion of this study is that toothpaste with a concentration of 50% is preferred over 25%.